DÍVIDA PÚBLICA E PASSIVO EXTERNO: onde está a ameaça? - Denise Lobato GentiI (Revista de Políticas Públicas, 2012)
This work aims to analyze if the trajectory and composition of net and gross, public debt and externai Iiabilities can hinder the growth of Brazilian GDP. The work concludes that fiscal indicators are more comfortable than externai indicators show. The net public debt is falling and it is less Iinked to exchange rate variations; the gross public debt is rising but it finances more public investment and public enterprises than monetary policy operations. Externai sector represent a bigger threat: net externai Iiabilities are growing allhough the recent externai assets accumulation; and the short run portion is growing too. The deficit in factor income is growing, and the trade balance is not able to generate surplus in the current accoun!. 80, Brazilian economy is more dependent of financiai f1ows, hence more dependent of externalliabilities.